ROTATION OF LONG TECTONIC CLASTS IN TRANSPRESSIONAL SHEAR ZONES - Ghosh S.K.; Sen G.; Sengupta S. (My University, 2003)
The two-dimensional analysis of rotation of rigid ellipsoidal inclusions is not applicable to situations in which either the bulk deformation deviates from plane-strain or one of the principal axes of the inclusion is at an angle to the vorticity vector. Both these situations may occur in certain types of transpressional ductile shear zones. The model presented here shows how long cylindrical or ellipsoidal tectonic clasts (with the longest axis parallel to the walls of the shear zone but at an angle to the vorticity vector) rotate in transpressional shear zones. Long clasts, initially at a low angle to the vorticity vector and at a large angle to the stretching lineation, will rotate and tend to become subparallel to the stretching lineation. The rotation of the principal axes of the elliptical cross-section around the cylinder axis cannot be unlimited for any inclusion, including the inclusion with circular cross-section (R=1); if the deformation is sufficiently large there is always a stable position of orientation. The model explains simultaneous occurrence of monoclinic rolling structures in sections parallel and perpendicular to the vorticity vector. Depending upon the initial orientation, the long axes of different clasts in the foliation plane may rotate clockwise and counterclockwise. Consequently, opposite senses of asymmetry of rolling structures may appear in sections parallel to the vorticity vector.
Keywords: ROTATION OF CLASTS; TRANSPRESSION; STRETCHING LINEATION